Performance of Multimode-Fiber Coupler with Different Coupler Parameter for Displacement Sensor - Samian Samian (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2010)
Three multimode-fiber couplers with different coupling ratios, excess losses and directivities are used to sense adisplacement. The fiber coupler is handmade from 1 mm diameter plastic optical fiber. The light source is 632.8nm He-Ne Laser. OPT 101 (Burr Brown) detector is used to detect the change in power output due to theobject’s displacement. The opted displacement’s resolution is 5 μm. The experiment shows that multimode-ficecoupler with 0.25 ratio, 1.37 dB excess loss, and 25 dB directivity gives the highest performance, which has 4mm dynamic range, 1 mm linear range, and 55.4 μW/mm sensitivity. Higher performance can be reached ifmultimode-fiber coupler with the highest coupling ratio and the lowest excess loss is opted.